Predicting shock-induced cavitation using machine learning: implications for blast-injury models - Marsh, Jenny L.; Zinnel, Laura; Bentil, Sarah A. (Frontiers in Bioengineering and Biotechnology, 2024)
While cavitation has been suspected as a mechanism of blast-induced traumatic brain injury for a number of years, the phenomenon remains difficult to study due to the current inability to measure cavitation in vivo. Therefore, numerical simulations are often implemented to study cavitation in the brain and surrounding fluids after blast exposure. However, these simulations need to be validated with the results from cavitation experiments. Machine learning algorithms have not generally been applied to study blast injury or biological cavitation models. However, such algorithms have concrete measures for optimization using fewer parameters than finite element or fluid dynamics models. Thus, making machine learning algorithms a viable option for predicting cavitation behavior from experiments and numerical simulations. This paper compares the ability of two machine learning algorithms, k-Nearest Neighbors (kNN) and Support Vector Machine (SVM), to predict shock-induced cavitation behavior. The machine learning models were trained and validated with experimental data from a three-dimensional shock tube model, and showed that the algorithms could predict the number of cavitation bubbles produced at a given temperature with good accuracy. This study demonstrates the potential utility of machine learning in studying shock-induced cavitation for applications in blast injury research.